Dinamika Psikologis Pelaku Pedofilia di Lapas Klas I Surabaya–Porong - Fatayati Citra Islami (Universitas Muhammadiyah Jember, 2021)
Paedophilia is a disorder in adult individuals with symptoms of having fantasies, urges, or behaviours that involve sexual activity in one or more children. Paedophilia cases are increasingly occurring in Indonesia and hurt children who are victims of paedophilia cases. Prevention of the occurrence of paedophilia can be suppressed through an in-depth understanding of the case description and the dynamics of paedophile perpetrators. The participant in this study was a 35-year-old man, a widower (divorced), having served a sentence of child molestation for one year in prison. This research uses a case study approach. This study found that there are factors that make the participants have the potential to cause pedophilic behaviour, namely parenting that tends to pamper, the sensitive personality of the perpetrator, lack of self-control, great need for affection, having an interest in things related to sex, difficulty in relationships, the absence of support from the environment, as well as the opportunity.